The effect of metabolic syndrome on outcome of acute exacerbation of chronic obstructive pulmonary disease (COPD) - Abo-bakr Al-Asmar (Al-Azhar University, Faculty of Medicine (Damietta), 2019)
Background: Metabolic syndrome is a multiorgan disease and it could aggravate other diseases. Its effect on chronic obstructive pulmonary disease needs to be addressed. Aim of the work:  to examine if metabolic syndrome increases the frequency, duration and severity of acute exacerbations of chronic obstructive pulmonary disease. Patients and methods: 60 patients who admitted with COPD exacerbation were included and were divided into two groups: Group 1 (COPD without metabolic syndrome). Group 2 (COPD with metabolic syndrome). All submitted to full history taking, clinical examination, laboratory and radiological examination. Results: COPD severity was GOLD class II in 25.0%, class III in 51.7% and class IV in 23.3%; and disease severity was significantly higher in patients with metabolic syndrome. The frequency of COPD exacerbations showed significant increase in group 2 when compared to group 1 (2.17±0.65 vs 1.43±0.57 respectively). In addition, the duration of hospital stay increased significantly in group 2 when compared to group 1 (4.33±0.80 vs 3.37±0.61). Conclusion: metabolic syndrome could play a role in pathogenesis- or may be a consequence of- COPD. Thus, metabolic syndrome had a harmful effect on the outcome of COPD exacerbations.